The effect of hyperbaric oxygen therapy on gene expression: microarray analysis on wound healing - Tlapák, Jakub; Chmátal, Petr; Oniscenko, Boris; Pavlík, Vojtech; Dosel, Petr; Páral, Jirí; Lochman, Petr (Undersea & hyperbaric medicine, 2020)
Background: Hyperbaric oxygen (HBO2) therapy can have a positive effect on wound healing, angiogenesis and blood flow. No prior study has described the effects of HBO2 therapy and gene expression of this process. The goal of our research was to show the effects of HBO2 and its impact at the molecular level on angiogenesis, proliferation, differentiation, oxidative stress, inflammation, and extracellular matrix formation. Live animal subjects were used for simulating the process of wound healing under standard conditions and under the influence of HBO2. Methods: Two experimental groups were created using injured rabbits (N=24), one group (N=12) treated with hyperbaric therapy twice a day and one (N=12) with standard wound care management. Wounds were surgical, uninfected, and in healthy animal test subjects. We compared the whole genomic analysis of the transcriptome with the use of microarray technology at three intervals during treatment. Results: The induction of the wounds in rabbit skin increased expression of hundreds of genes in both treatment groups. The numbers of elevated and decreased genes gradually reduced as the wound healed. Gene expression analysis showed elevated expression of several genes associated with inflammation in both groups of injured animals. Genes connected to the process of angiogenesis, proliferation, differentiation, oxidative stress and extracellular matrix formation were without statistically significant changes. Conclusion: The evidence did not support that HBO2 had any significant effect on gene expression during wound healing. Additionally, there was no evidence to support that there were changes in gene expression in either treatment group.
Keywords: Surgical Wound; Animals; Tissue Array Analysis; Rabbits; Female; hyperbarická oxygenace; ženské pohlaví; Wound Healing; kůže; messenger RNA; čipová analýza tkání; RNA, Messenger; Skin; hojení ran; exprese genu; králíci; chirurgická rána; zvířata; Hyperbaric Oxygenation; Gene Expression